The Never-Ending Poxes of Syphilis, AIDS, and Measles - Bastos, Cristiana (Centaurus, 2022)
Abstract In this article, I address some infectious diseases that never really “ended,” even though their morbidity, their social impact, and their public visibility have faded away: AIDS, syphilis, and measles. I will use data from different projects I have conducted on each of those epidemics: HIV/AIDS at the doctoral training level in the 1990s, with a geographical focus on Brazil and the United States; syphilis in the context of a 2010 project on the social history of health in Lisbon in the late 19th and early 20th centuries; and measles as part of my current project on labor migration in the 19th century, with a focus on epidemic outbreaks in migrant ships from Madeira to Hawaii.